Ginsenoside Rg18 suppresses lipopolysaccharide-induced neuroinflammation in BV2 microglia and amyloid-β-induced oxidative stress in SH-SY5Y neurons via nuclear factor erythroid 2-related factor 2/heme oxygenase-1 induction. (April 2017) - Kim, Mina; Choi, Sang Yoon; Kim, Kyung-Tak; Rhee, Young Kyoung; Hur, Jinyoung
Highlights: Ginsenoside Rg18 (NGA) is newly identified as a key constituent of Panax ginseng. NGA decreased LPS-mediated activation of microglial cells through p38 signalling. NGA protected against Aβ cytotoxicity in SH-SY5Y neuronal cells. Neuronal protection was associated with increased Akt-ERK1/2 signalling. NGA have crucial role as a neuroprotective agent for neurodegenerative disorders. Abstract: Neurodegenerative disease states are typified by the presence of activated microglia and maladaptive neuron-microglia interactions. Thus, there is a need for agents that target pathological cell-cell interactions. We tested the hypothesis that ginsenoside Rg18 (NGA), a constituent of Panax ginseng root, in part mediates the beneficial effects of Panax ginseng . In lipopolysaccharide-stimulated BV2 microglia, NGA decreased the expression of cyclooxygenase-2, tumour necrosis factor-α, IL-1β and inducible nitric oxide synthase as well as NO synthesis. NGA also inhibited p38 mitogen-activated protein kinase and STAT1 phosphorylation. In SH-SY5Y neurons subjected to amyloid-beta (Aβ) oligomer cytotoxicity, NGA promoted cell viability and up-regulated nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) in a manner associated with Akt/ERK1/2 activation. Taken together, these results suggest that NGA is a functional food constituent that exerts neuroprotective effects.